ANALYSIS OF MEMBRANE DEVICES CONSTRUCTIONS OF THE FOOD AND PROCESSING INDUSTRY (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
An analysis of modern designs of membrane devices, which are used at enterprises of the food and processing industry, was carried out. The need for a wider use of membrane technologies for the processing of food liquids is substantiated. In particular, the processes of concentration and illumination. Characteristic shortcomings of baromembrane processes are identified. The conducted analytical studies made it possible to conclude that membranes with a larger pore diameter do not allow obtaining the required degree of illumination. Membranes with a smaller pore size are characterized by low permeability.
Keywords: microfiltration; ultrafiltration; reverse osmosis; membrane treatment; baromembrane processes; membrane devices; food industry